2018
DOI: 10.3389/fcvm.2018.00031
|View full text |Cite
|
Sign up to set email alerts
|

Can Blood Biomarkers Help Predicting Outcome in Transcatheter Aortic Valve Implantation?

Abstract: Transcatheter aortic valve implantation (TAVI) has become the method of choice for patients with severe aortic valve stenosis, who are ineligible or at high risk for surgery. In this high risk patient population, early and late mortality and rehospitalization rates after TAVI are still relatively high. In spite of recent improvements in procedural TAVI, and establishment of risk models for poor outcome, determining individual risk remains challenging. In this context, current data from several small studies st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In view of these considerations, several groups have been encouraged to investigate whether imaging or circulating biomarkers can improve risk stratification in TAVR, including cardiac troponins, brain natriuretic peptides, growth differentiation factor‐15 (GDF‐15), among others 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…In view of these considerations, several groups have been encouraged to investigate whether imaging or circulating biomarkers can improve risk stratification in TAVR, including cardiac troponins, brain natriuretic peptides, growth differentiation factor‐15 (GDF‐15), among others 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, biomarkers have emerged as important tools for these roles in varied cardiovascular diseases including patients with severe aortic stenosis prior to the intervention. As such, several promising biomarkers are under scientific investigation for clinical application, including proBNP [39], NT-proBNP [15,[40][41][42][43][44][45], BNP [45,46], CRP [45,46], cardiac troponin [45], microRNA [46], von Willebrand factor [45], GAL-3, MPV, and others [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already identified clinical parameters and biomarkers that may improve patient risk stratification (e.g. CK-MB, high-sensitivity Troponin T, BNP and NT-proBNP) [ 6 ]. In addition, there are also surgical risk prediction models such as the logistic EuroSCORE (Log ES), its revised and updated version EuroSCORE II, and the Society of Thoracic Surgeons (STS) score [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%